CARDIO-ONCOLOGY IN TREATMENT AND REHABILITATION PROGRAMS OF ONCOLOGICAL PATIENTS - M. F. Balluzek; A. K. Ionova (Российский кардиологический журнал, 2014)
While studying the nearest and distant consequences of chemo- and radiation therapy, systemic effects of cancer on human, frequent comorbidity, a control of the state of cardiovascular system in all of the stages of medical cancer treatment become necessary. A classification of cardiological and cardiotoxic events, which are common in treatment of cancer, is provided. The need of development of the new interdisciplinary direction — cardio-oncology — in algorithm of treatment and rehabilitation process is revealed.